2003
DOI: 10.1046/j.1365-2036.2003.01768.x
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of oesophageal acid exposure distinguish complicated reflux disease from either erosive reflux oesophagitis or non‐erosive reflux disease

Abstract: SummaryBackground : The reason why less than one‐half of patients with gastro‐oesophageal reflux disease develop complicated reflux disease (ulcerative oesophagitis, oesophageal strictures and Barrett's oesophagus) and erosive reflux oesophagitis is not fully understood. Supine nocturnal oesophageal acid reflux is considered to be critically involved in this phenomenon, but reliable data are lacking.Aim : To clarify whether high levels of supine nocturnal oesophageal acid exposure are associated with complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
60
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 46 publications
(69 reference statements)
12
60
1
4
Order By: Relevance
“…This correlates with the observation that the severity of esophagitis correlates with amount of acid exposure 33 and similar findings have been reported by others. 25 The composite (DeMeester) score, which includes all the acid reflux measures in a weighted calculation of reflux severity, discriminated most clearly between the different GERD stages in this and a similar study. 34 We have presented the findings without applying a correction for multiple comparisons; thus, one explanation is that they are false positive results due to chance alone.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This correlates with the observation that the severity of esophagitis correlates with amount of acid exposure 33 and similar findings have been reported by others. 25 The composite (DeMeester) score, which includes all the acid reflux measures in a weighted calculation of reflux severity, discriminated most clearly between the different GERD stages in this and a similar study. 34 We have presented the findings without applying a correction for multiple comparisons; thus, one explanation is that they are false positive results due to chance alone.…”
Section: Discussionsupporting
confidence: 51%
“…It is well recognized that hiatal hernia is present in most patients with BE, and a lower frequency of hernia in patients with NERD has been reported. 4,24,25 In a large case control study, the presence and size of hernia was strongly associated with risk of developing high grade dysplasia or adenocarcinoma in patients with BE. 26 Hiatal hernia has also be identified as an important factor for the development of ERD in patients with NERD.…”
Section: Discussionmentioning
confidence: 99%
“…A tendency for NERD+ patients to have a higher mean LES pressure than ERD patients has also been reported in other studies, although the difference failed to reach statistical significance [14,20] . Findings for esophageal body motility did not differ significantly between patients with NERD+ and those with ERD, apart from a slight tendency for the distal wave amplitude to be greater in the first group.…”
Section: Physiopathological Patternsupporting
confidence: 74%
“…In particular, the fact that the mean age of the ERD group was similar to that of the NERD+ patients (around 50 years old in both cases) seems to contradict the claim that patients with- out esophagitis tend to be younger and can be expected to progress towards a picture of full-blown esophagitis as they grow older [12,13] . Other authors reported individuals with complicated reflux disease being older than patients with NERD+, although the latter were actually much the same age as the group with ERD, as in our population [14] . We also found no gender-related differences in our two patient groups despite the literature reporting a tendency to find more females among NERD patients than among cases of esophagitis [12,15,16] .…”
Section: General Considerations: Study Populationsupporting
confidence: 54%
See 1 more Smart Citation